Workshop Strategi Pemasaran Produk Olahan Kedelai di Teluk Betung, Kota Bandar Lampung - Rizka Malia; Nindya Eka Sobita; Mega Mariska; Muhammad Mufti Hudani; I Wayan Suparta (Lembaga Pengembangan Kinerja Dosen, 2025)
Tempe artisans in Teluk Betung District, Bandar Lampung City play an important role in providing soybean-based food products. However, the marketing of their products is still conducted conventionally, relying on traditional markets and simple promotional methods, which limits market reach and reduces product competitiveness. This community service activity aims to improve the knowledge and skills of tempe artisans in implementing effective marketing strategies, particularly through digital platforms and product packaging development. The methods used included interactive lectures, group discussions, social media simulations, and practical sessions on designing product labels using simple applications. The workshop results showed that most participants successfully created business social media accounts, designed product labels, and understood the importance of attractive packaging in increasing product value. This activity is expected to serve as a stimulus for developing tempe product marketing in Teluk Betung and surrounding areas.